Refractory Crohn’s Disease of the Vulva Treated with Infliximab: A Case Report - Sapna Makhija; Martin Trotter; Elizabeth Wagner; Sylvain Coderre; Remo Panaccione (Canadian Journal of Gastroenterology)
Crohn’s disease (CD) is a chronic relapsing and remitting inflammatory disorder of the gastrointestinal tract. The common presentation includes abdominal pain, abdominal cramping and diarrhea. Many patients may exhibit systemic symptoms of fever and weight loss. Approximately 20% to 40% of patients will experience extraintestinal manifestations that involve the eyes, skin and joints. Women may experience a variety of gynecological manifestations, including vulvovaginal involvement, which is often not recognized and also difficult to treat. A case of refractory vulvovaginal CD is presented and the literature of gynecological manifestations of CD and its treatment are reviewed.